Optimization method for estimating tissue microstructure size-distributions with diffusion weighted imaging - Pablo Jiménez (2023)
Digital Poster at the Annual Meeting of the International Society for Magnetic Resonance in Medicine ISMRM-ISMRTCharacterization of microstructures in living-tissues by non-invasive imaging is one of the key and outstanding challenges for diagnosing early stages of pathologies and understanding disease mechanisms. Here we implement an optimal control strategy for obtaining microstructure details by Diffusion-Weighted Imaging sequences. We estimate microstructure parameters of size-distribution models for axon bundles, attaining the ultimate precision limits predicted by quantum-information tools. We performed proof-of-principle experiments of the optimization protocol with an ex-vivo mouse-brain contrasted with simulations. These results might drastically reduce the total acquisition time compared to the present state-of-the-art, opening alternative avenues towards unraveling diagnostic information by quantitative MRI.